2020
DOI: 10.2319/061819-415.1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of structural skeletal asymmetry of the glenoid fossa in adult patients with unilateral posterior crossbite using surface-to-surface matching on CBCT images

Abstract: Objectives To compare, using surface-to-surface (StS) matching, any shape differences between the crossbite and noncrossbite side of the glenoid fossa and articular eminence in adult patients affected by posterior unilateral crossbite (PUXB) and compare them with unaffected controls. Materials and Methods 32 cone beam computed tomography (CBCT) scans of patients (mean age: 23.72 ± 3.74 years) undergoing surgical maxillary exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 21 publications
1
19
0
Order By: Relevance
“…Although our study described side asymmetry between the control and crossbite groups, it aligns with previous studies regarding the relationship between the symmetric condyle glenoid fossa of the crossbite and non‐crossbite sides in patients with untreated posterior crossbites, which could be explained by skeletal remodelling of the TMJs and/or variation in the thickness of the articular TMJ disc, as described by Muraglie, Hesse, Bishara and Wang 20,25,45,46 . Those studies suggest that the TMJ disc can adapt to any alteration caused by occlusal changes to the space between the condyle and fossa.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Although our study described side asymmetry between the control and crossbite groups, it aligns with previous studies regarding the relationship between the symmetric condyle glenoid fossa of the crossbite and non‐crossbite sides in patients with untreated posterior crossbites, which could be explained by skeletal remodelling of the TMJs and/or variation in the thickness of the articular TMJ disc, as described by Muraglie, Hesse, Bishara and Wang 20,25,45,46 . Those studies suggest that the TMJ disc can adapt to any alteration caused by occlusal changes to the space between the condyle and fossa.…”
Section: Discussionsupporting
confidence: 91%
“…The first method showed that the linear measurements of the crossbite and aligned sides in the UCG and the right and left sides in the other groups were not statistically different except the medial condylar position was significantly greater in the CG and BCG and the CG and UCG on both the right and left sides, likely due to the nearly linear differences (condyle width, height and total volume) between the groups. Muraglie et al 25 found that a higher percentage of glenoid fossa and articular eminence asymmetry was found while comparing the crossbite and non‐crossbite sides of PUXB patients compared with the control sample, with mean percentage differences greater than 11 for each level of tolerance. These findings further corroborate the adaptive nature of the glenoid fossa even in PUXB patients, which is known to occur after changes in the occlusion and positioning of the mandible.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The possibility to simulate a virtual patient represents an important step towards a personalized diagnostic and therapeutic approach [44][45][46]. Future investigations would focus on the analysis of the effective clinical advantages that the patient can get from a simplified digital planning.…”
Section: Discussionmentioning
confidence: 99%